Advanced glycation end‐products accelerate the cardiac aging process through the receptor for advanced glycation end‐products/transforming growth factor‐β‐Smad signaling pathway in cardiac fibroblasts. Issue 4 (28th May 2015) - Fang, Min; Wang, Junhong; Li, Shiling; Guo, Yan
Abstract : Aims: The current study was carried out to evaluate the effect of advanced glycation end‐products (AGE) on cardiac aging and to explore its underlying mechanisms. Methods: Neonatal rat cardiac fibroblasts were cultured and divided into four groups: control; AGE; AGE + receptor for AGE antibody and AGE + SB431542 (transforming growth factor‐β [TGF‐β]/Smad signaling pathway inhibitor, 10 μmol/L) group. After being cultured for 48 h, the cells were harvested and the senescence‐associated beta‐galactosidase expression was analyzed. Then the level of p16, TGF‐β, Smad/p‐smad and matrix metalloproteinases‐2 was evaluated by western blot. Results: Significantly increased senescence‐associated beta‐galactosidase activity as well as p16 level was observed in the AGE group. Furthermore, AGE also significantly increased the TGF‐β1, p‐smad2/3 and metalloproteinases‐2 expression in cardiac fibroblasts (all P  < 0.01). Meanwhile, either pretreatment with receptor for AGE‐Ab or SB431542 significantly inhibited the upregulated cardiac senescence (beta‐galactosidase activity and P16) and fibrosis‐associated (TGF‐β1, p‐smad2/3 and metalloproteinases‐2) markers induced by AGE. Conclusions: Taken together, all these results suggested that AGE are an important factor for cardiac aging and fibrosis, whereas the receptor for AGE and TGF‐β/Smad signaling pathway might be involved in the AGE‐induced cardiac aging process.Geriatr Gerontol Int 2016; 16: 522‐527.